Influence of the segmentation method – automatic vs manual – and the presence or not of extra myocardial activity in quantification of defect extent in SPECT myocardial studies - Machado, Marisa (2022)
Introduction – Myocardial Perfusion Imaging (MPI) by single-photon emission computed tomography (SPECT) is one of the most widely used Non-invasive imaging tests in the diagnosis of coronary artery disease that requires correct segmentation of the left ventricle (LV), to extract perfusion parameters. The aim of this study is to evaluate the influence of automatic (A) vs. manual (M) segmentation in the quantification of defect extent (DE) of myocardial perfusion, in studies with and without extra myocardial activity. Methodology – A retrospective study with a non-probabilistic sample was used, for convenience, of 63 stress studies, with the indication for MPI available in the Xeleris® workstation database in ESTeSL, that were divided into four groups: Group (G) I (GI): 26 studies by presenting a DE below 10% of the total surface area of the LV; Group II (GII): 5 studies with a DE equal or above 10%; Group III (GIII): 21 studies with a DE below 10%, with extra myocardial activity and Group IV (GIV): 11 studies with a DE, with extra myocardial activity. All studies were segmented, by one operator, using the A and the M quantification software Quantitative Perfusion SPECT (QPS®). For data analysis from the map polar with 20 segments were used t-Student, Wilcoxon, and U de Mann-Whitney tests considered α=0.05. Results – Concerning the perfusion DE evaluation it was verified that there were statistically significant differences (p>α) between the A vs. M segmentation, in segments 13-15 (GI); segments 13 and 16 (GIII), and segments 1 and 16 (GIV). Regarding the studies with and without extra myocardial activity, it was observed that no statistically significant variability exists (p>α). Conclusion – On the basis of the sample analyzed there are differences between an A vs M segmentation in peripheral segments of the polar map, in myocardial perfusion ED evaluation. There are no differences between myocardial perfusion DE in studies with and without extra myocardial activity.